Factors Influencing Tax Avoidance : An Empirical Study on the Indonesian Stock Exchange - Fajar Nurdin; Nadia Nadia (Journal of Accounting Auditing and Business, 2022)
The study aimed to determine the effect of returns on assets, leverage, and political connections to the level of tax avoidance . This research was conducted on food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sample collection technique is purposive sampling and obtained a total of  11 companies.  The type of data used is secondary data in the form of the company's annual financial statements obtained from the IDX website or the company's website .  Data analysis uses multiple linear regression tests with the help of SPSS software version 20. The  results of tests that have been done stated that the return on assets has a significant negative effect on tax avoidance. While leverage and political connections have a significant positive effect on tax avoidance.  Simultaneous  returns on assets, leverage ,and political connections affect tax avoidance, with an influence rate of 35.6% while the remaining 64.4% can be described by other independent variables not included in the study